2016
DOI: 10.1371/journal.pone.0162960
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Disparities in Adults with Type 1 Diabetes: More Than a Quality of Care Issue. A Cross-Sectional Observational Study from the AMD Annals Initiative

Abstract: We evaluated gender-differences in quality of type 1 diabetes (T1DM) care. Starting from electronic medical records of 300 centers, 5 process indicators, 3 favorable and 6 unfavorable intermediate outcomes, 6 treatment intensity/appropriateness measures and an overall quality score were measured. The likelihood of women vs. men (reference class) to be monitored, to reach outcomes, or to be treated has been investigated through multilevel logistic regression analyses; results are expressed as Odd Ratios (ORs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 25 publications
(46 reference statements)
9
30
2
2
Order By: Relevance
“…When evaluating quality of diabetes care, through the Q score [ 15 , 16 ], we found an overall good quality of care (mean values of 29–30) at different age- and DKD strata, and these data are in line with the findings of other diabetic cohorts in Italy [ 15 , 16 ]. However, older subjects (> 75 years) and those with albuminuria (Alb+) showed lower Q score values compared to the other groups.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…When evaluating quality of diabetes care, through the Q score [ 15 , 16 ], we found an overall good quality of care (mean values of 29–30) at different age- and DKD strata, and these data are in line with the findings of other diabetic cohorts in Italy [ 15 , 16 ]. However, older subjects (> 75 years) and those with albuminuria (Alb+) showed lower Q score values compared to the other groups.…”
Section: Discussionsupporting
confidence: 81%
“…Quality of care was assessed through a validate score, the Q score [ 15 , 16 ], which is calculated on a combination of process and outcome indicators, based on levels and treatment of major CVD risk factors (HbA1c, blood pressure, LDL-cholesterol and albuminuria), assigning the highest score when the desired goals were attained, whereas the lowest score was assigned when the patient was not treated for the specific condition despite elevated values or when the patient showed unsatisfactory values despite the treatment. Overall, Q score ranges between 0 and 40, with a higher score reflecting better quality of care.…”
Section: Methodsmentioning
confidence: 99%
“…Italian data from annals published by Associazione Medici Diabetologi (AMD), the Italian association of diabetologists, showed that diabetic women had 14% higher chance of having HbA1c > 9% regardless of insulin therapy, 42% more likely to have low-density lipoprotein (LDL) cholesterol > 130 mg/dL irrespective of statin therapy, and 50% greater chance of having BMI > 30 kg/m 2 [ 48 , 49 ]. These data seem to be partially confirmed in type 1 diabetic patients, in whom women showed worse metabolic control and men had higher blood pressure [ 13 ]. Furthermore, diabetic women, regardless of menopausal state, present significantly higher risk of ischemic cardiomyopathy than diabetic men.…”
Section: Sex Hormones In Endocrine Gender-related Differencesmentioning
confidence: 90%
“…As a consequence, in addition to the typical differences of sex directly induced by hormones, we also have to consider the drug peripheral distribution and transformation pathways, especially hepatic and renal, which may be responsible for their reduced or increased efficacy as well as of the appearance of adverse reactions, for example due to their inappropriate doses or ways of administration. Moreover, socioeconomic and cultural contexts may represent additional confounding factors being able to influence the epidemiological characteristics of diseases, the approach, and the response to specific therapeutic treatments [ 9 , 10 , 13 , 15 ].…”
Section: Sex Hormones In Endocrine Gender-related Differencesmentioning
confidence: 99%
“…There are few and discordant data on the prevalence of FSD in diabetic women due to differences in methodology (face-to-face interviews, mail questionnaires, telephone interviews), sample size definition and classification of severity of the disease. The prevalence of type 1 diabetes in Italy is equal to 0.3%; 50.4% of women with type 1 diabetes are of childbearing age (15-45 years) [10].…”
Section: Introductionmentioning
confidence: 99%